The Emerging Role of Extracellular Vesicle-Mediated Drug Resistance in Cancers: Implications in Advanced Prostate Cancer. (26th October 2015) - Soekmadji, Carolina; Nelson, Colleen C.
Abstract : Emerging evidence has shown that the extracellular vesicles (EVs) regulate various biological processes and can control cell proliferation and survival, as well as being involved in normal cell development and diseases such as cancers. In cancer treatment, development of acquired drug resistance phenotype is a serious issue. Recently it has been shown that the presence of multidrug resistance proteins such as Pgp-1 and enrichment of the lipid ceramide in EVs could have a role in mediating drug resistance. EVs could also mediate multidrug resistance through uptake of drugs in vesicles and thus limit the bioavailability of drugs to treat cancer cells. In this review, we discussed the emerging evidence of the role EVs play in mediating drug resistance in cancers and in particular the role of EVs mediating drug resistance in advanced prostate cancer. The role of EV-associated multidrug resistance proteins, miRNA, mRNA, and lipid as well as the potential interaction(s) among these factors was probed. Lastly, we provide an overview of the current available treatments for advanced prostate cancer, considering where EVs may mediate the development of resistance against these drugs.